Sulfur hexafluoride degradation catalyst as well as preparation method and application thereof

By doping aluminum and cerium atoms in the molecular sieve catalyst and combining hydrolysis and oxidation reactions, the problems of high temperature and high product toxicity of the existing SF6 degradation catalyst are solved, and the low-temperature efficient degradation and easy-to-treat products of SF6 are achieved, reducing the preparation cost.

CN119588411APending Publication Date: 2025-03-11ZJU-ANQING YANGTZE DELTA FUTURE IND INSTITUTE +1

Patent Information

Application Number
CN202411551439.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing SF6 degradation catalysts have problems such as high catalytic temperature, high toxicity and difficulty in dealing with the degradation product, and low recycling rate.

Method used

The doped molecular sieve catalyst is prepared by hydrothermal method, and the low-temperature degradation of SF6 is achieved through aluminum and/or cerium atom doping modification, combined with hydrolysis and oxidation reactions.

Benefits of technology

It realizes the efficient low-temperature degradation of SF6, the degradation products are easy to handle, the catalyst preparation process is simple, the use cost is low, and the SO2 selectivity is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005115187240000071
    Figure BDA0005115187240000071
  • Figure BDA0005115187240000072
    Figure BDA0005115187240000072
Patent Text Reader

Abstract

The invention discloses a sulfur hexafluoride degradation catalyst as well as a preparation method and application thereof in catalytic degradation of SF6 (sulfur hexafluoride). The preparation method comprises the following steps: (1) adding pseudo-boehmite and / or cerous nitrate into deionized water to be fully dissolved, and stirring to be in an emulsion or solution state; sequentially adding phosphoric acid, a silicon source and a template agent while stirring, and adjusting the pH value of the mixed solution to 5.0-6.5; (2) stirring and evaporating moisture in the mixed solution obtained in the step (1), and further drying to obtain dry glue; grinding the dry glue, putting the ground dry glue into a crystallization kettle, crystallizing at 200-210 DEG C, washing a crystallized product to be neutral, drying, and calcining to remove the template agent, so as to obtain the Al and / or Ce doped SF6 degradation catalyst. The catalyst is used for catalytic degradation of sulfur hexafluoride and is low in catalytic temperature, excellent in degradation effect, excellent in SO2 selectivity, small in product harm, easy to treat, simple in catalyst preparation process and low in use cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental catalysis, and in particular to a sulfur hexafluoride degradation catalyst and a preparation method and application thereof. Background Art

[0002] SF6 is a non-toxic, colorless, odorless, high-density gas. With its excellent chemical stability and dielectric strength, it has good insulation and arc-extinguishing properties. It is widely used in power transmission and transformation equipment, magnesium and aluminum metal smelting, atmospheric tracing, electronic manufacturing, etc. in the power industry. According to statistics, the power industry consumes 80% of SF6 production, which is mainly used in circuit breakers, high-voltage switches, high-voltage transformers, gas-enclosed combination capacitors, high-voltage transmission lines, mutual inductors, etc.

[0003] SF6 has a very strong ability to absorb infrared radiation. Its greenhouse effect is 24,000 times that of carbon dioxide and it can exist stably in the atmospheric environment for 3,200 years. Therefore, SF6 control is particularly necessary.

[0004] SF6 is widely used in many industries, and its emission status is quite severe. At present, the recycling rate of SF6 is still very low, and most of the recycled SF6 gas eventually escapes into the atmosphere after limited use. It is currently impossible to collect and decompose the SF6 gas that escapes into the atmosphere. In the final analysis, the degradation and removal rate of the emitted SF6 is very low.

[0005] SF6 has a regular octahedral molecular structure and its chemical properties are very stable. Currently, the degradation technologies for SF6 mainly include pyrolysis, photolysis, plasma, etc. The pyrolysis method requires the reactor to be heated to above 1100°C for high-temperature pyrolysis, while by adding a catalyst, the catalytic reaction temperature can be reduced to a lower temperature, thereby achieving the purpose of degrading SF6 and saving fuel, thereby reducing the processing cost.

[0006] The sulfur hexafluoride degradation catalysts currently in the research stage mainly include metal phosphates, supported metal catalysts, metal oxides, etc. The patent specification with the announcement number CN100389857C discloses an alumina catalyst that can catalytically decompose SF6, and the phosphorus component is loaded on the surface of the alumina, and the loading method is impregnation and calcination. The patent specification with the announcement number CN110124512B discloses a method for treating sulfur hexafluoride waste gas, first using a defluorinating agent to crack sulfur hexafluoride, the defluorinating agent is a mixture of modified mesoporous molecular sieves and silicon powder, and the modified mesoporous molecular sieve is a mesoporous molecular sieve modified by alkali metal fluorides and alkaline earth metal oxides. The cracking reaction tail gas is then passed through type A molecular sieves and activated carbon in turn and then discharged harmlessly. In addition, the more popular metal phosphates include cerium phosphate, aluminum phosphate, zirconium phosphate, etc. Studies have shown that specific metal phosphates have different effects on the catalytic degradation of SF6, which are manifested in the SF6 degradation rate, degradation temperature, etc.

[0007] Currently, the more popular phosphate degradation catalysts still have problems, as listed below:

[0008] 1) The working temperature of cerium phosphate catalyst is still relatively high;

[0009] 2) After SF6 is degraded by aluminum phosphate catalyst, the degradation products have certain toxicity and are difficult to handle. Improper subsequent treatment will still cause secondary pollution. Summary of the invention

[0010] In view of the above technical problems and the deficiencies in the art, the present invention provides a sulfur hexafluoride degradation catalyst and a preparation method and application thereof.

[0011] The present invention provides an efficient and green SF6 degradation catalyst, which is a molecular sieve catalyst. The catalyst can achieve the purpose of completely degrading and eliminating SF6 by combining hydrolysis reaction with oxidation reaction. The catalyst has the advantages of low catalytic temperature, excellent degradation effect, excellent SO2 selectivity, small harm of secondary pollutants and easy treatment, simple catalyst preparation process, low use cost, etc.

[0012] [1] A method for preparing a sulfur hexafluoride degradation catalyst, comprising the steps of:

[0013] (1) adding pseudo-boehmite and / or cerium nitrate into deionized water to fully dissolve, and stirring until an emulsion or solution is formed; then adding phosphoric acid, a silicon source and a template agent in sequence under stirring, and adjusting the pH value of the mixed solution to 5.0-6.5;

[0014] (2) stirring and evaporating the water in the mixed solution obtained in step (1), and further drying to obtain a dry glue; grinding the dry glue and placing it in a crystallization kettle, crystallizing at 200-210° C., washing the crystallized product to neutrality and then drying it, calcining it to remove the template agent, and obtaining an Al and / or Ce doped SF6 degradation catalyst.

[0015] The present invention adopts a hydrothermal method to introduce cerium and / or aluminum atoms into a molecular sieve to prepare a doped molecular sieve catalyst, and a silicon source (specifically, a sol liquid, etc.), a template agent, etc. are successively added and continuously stirred. After being fully mixed (in a water bath), the mixed liquid is evaporated to dryness and dried to a dry gel state, and then crystallized, washed, dried, and calcined to prepare an SF6 degradation catalyst.

[0016] The sulfur hexafluoride degradation catalyst of the present invention is essentially a molecular sieve, which is modified by doping with aluminum atoms and / or cerium atoms, and exhibits excellent sulfur hexafluoride degradation effect. Cerium and aluminum are doped in different proportions, and preferably, when the total molar amount of (Ce+Al) is kept unchanged and the aluminum:cerium doping ratio is 7:1 (molar ratio), the best sulfur hexafluoride degradation performance at a lower temperature is exhibited.

[0017] In step (1), pseudo-boehmite and cerium nitrate may be added in an Al:Ce molar ratio of 10:(1-4).

[0018] In step (1), pseudo-boehmite and cerium nitrate are preferably added in an Al:Ce molar ratio of 7:1, and the resulting catalyst has the best SF6 degradation performance.

[0019] In step (1), the mass content of Al2O3 in the pseudo-boehmite may be 65% to 70%.

[0020] In step (1), the conductivity of the deionized water may be no greater than 20.0 μS / cm.

[0021] In step (1), you can press PO4 3- :(Al 3+ +Ce 3+ ) Phosphoric acid is added in a molar ratio (0.98-1.02):1, preferably 1:1.

[0022] In step (1), phosphoric acid may be added in the form of a phosphoric acid solution.

[0023] In step (1), the mass content of phosphoric acid in the phosphoric acid solution may be not less than 85%.

[0024] In step (1), you can press Si 4+ :(Al 3+ +Ce 3+ )The silicon source is added in a molar ratio of (0.95-1.05):5, preferably 1:5.

[0025] In step (1), the silicon source may be at least one of acidic silica sol and tetraethyl orthosilicate.

[0026] In step (1), the pH of the acidic silica sol may be 2.2 to 3.6.

[0027] In step (1), the mass content of SiO2 in the acidic silica sol can be 29% to 31%.

[0028] In step (1), the template can be: (Al 3+ +Ce 3+ ) The template is added in a molar ratio of 2:(1~1.05) preferably 2:1.

[0029] In step (1), the template agent may be at least one of di-n-propylamine and diisopropylamine.

[0030] In step (1), at least one of di-n-propylamine and diisopropylamine can be used to adjust the pH value of the mixed solution.

[0031] In step (2), the crystallization time at 200-210° C. can be 20 h to 24 h, preferably 24 h.

[0032] In step (2), the heating rate of the calcination can be 5 to 8°C / min, the insulation temperature can be 550 to 600°C, and the insulation time can be 4 to 5 hours.

[0033] [2] An Al and / or Ce doped SF6 degradation catalyst prepared according to the preparation method described in [1].

[0034] [3] Use of the Al and / or Ce doped SF6 degradation catalyst according to [2] in catalytic degradation of SF6. The catalytic degradation temperature may be 500 to 800° C., and further may be 600 to 800° C. During the catalytic degradation process, H2O and / or O2 may also exist in the catalytic degradation environment.

[0035] [4] A method for catalytic degradation of SF6, comprising: passing a mixed gas containing SF6 through the Al and / or Ce doped SF6 degradation catalyst described in [2], to catalytically degrade SF6. The mixed gas may contain H2O and / or O2. The temperature of the catalytic degradation may be 500 to 800°C, and further may be 600 to 800°C.

[0036] The sulfur hexafluoride degradation catalyst prepared by the invention can degrade sulfur hexafluoride at a relatively low temperature with high efficiency, and the degradation product is easy to handle.

[0037] In the application described in [3] and the method described in [4], for example:

[0038] The sulfur hexafluoride concentration in the treated sulfur hexafluoride-containing mixed gas may be 0.5-2.0 vol.%, the oxygen concentration may be 0.5-2.0 vol.%, the water vapor concentration may be 1.0-20 vol.%, and the rest may be nitrogen or the like.

[0039] In the thermal decomposition method, the SF chemical bonds in SF6 break at high temperatures (above 1100°C) and then rebond with hydrogen atoms and oxygen atoms, resulting in the degradation and elimination of SF6.

[0040] In the catalytic degradation method, the SF bond in sulfur hexafluoride can be broken at a lower temperature because the catalyst can reduce the reaction energy barrier during the reaction, so that the reaction can be carried out at a lower temperature.

[0041] The catalyst in the present invention is prepared in the form of a molecular sieve and participates in the degradation reaction to form an Al and / or Ce doped molecular sieve structure, thereby preparing a molecular sieve catalyst with a lower silicon-aluminum ratio or no aluminum, and having more The number of acid centers, which can adsorb SF6, H2O, etc.

[0042] After calcination, there are a large number of exposed lattice metal ion sites on the catalyst surface. In the presence of water vapor, the lattice metal ion sites on the catalyst surface undergo hydroxylation to form a large number of surface hydroxyl groups. SF6 is cracked under the action of the surface hydroxyl groups and is thus removed.

[0043] In some cases of the present invention, a cerium source is added to dope Ce atoms into the molecular sieve. The addition of Ce atoms makes the reaction more in-depth, and the product can be SO x F y Further converted to SO x , thereby increasing the catalyst’s SO x (especially SO2) selectivity.

[0044] The present invention utilizes phosphoric acid to assist in the preparation of molecular sieve catalysts and to activate them, so that a large number of cavities are formed on the surface of the molecular sieve and active acid sites exist.

[0045] The present invention uses a template to guide the growth of the framework and promote the formation of the molecular sieve framework. After calcination, the template is removed, the pore volume in the crystal is released, and the conditions for adsorption and catalysis are formed.

[0046] The present invention adjusts the pH value of the mixed solution during the preparation process to balance the charge of the catalyst skeleton.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The catalyst of the invention is used for catalytic degradation of sulfur hexafluoride, has low catalytic temperature, excellent degradation effect, excellent SO2 selectivity, low product hazard and easy treatment, simple catalyst preparation process and low use cost.

[0049] Compared with the prior art invention, the catalyst of the present invention has high selectivity while maintaining high degradation performance. The introduction of cerium atoms has a great effect on improving the catalyst SO x Selectivity is particularly critical. At the same time, the catalyst preparation steps of the present invention omit the node of special preparation of the carrier, which has a greater advantage in reducing the preparation cost. DETAILED DESCRIPTION

[0050] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0051] Unless otherwise specified, the pH of the acidic silica sol used in the following examples and comparative examples is 2.2-3.6, and the mass content of SiO2 is 30%.

[0052] Example 1

[0053] 1. Catalyst preparation:

[0054] The preparation method of the SF6 degradation catalyst involved in this embodiment includes the following steps.

[0055] (1) Maintain 3+ +Ce 3+ ) total molar concentration remains unchanged, pseudo-boehmite (Al2O3 content 70wt%) and cerium nitrate are added into appropriate amount of deionized water at Al:Ce molar ratio of 10:1 to fully dissolve, and the solution is stirred vigorously until it becomes a white emulsion; phosphoric acid solution is added at PO4 3- :(Al 3+ +Ce 3+ ) was added to the white emulsion in a molar ratio of 1:1 and stirred vigorously; acidic silica sol (pH 2.2-3.6, SiO2 mass content 30%) was added according to Si 4+ :(Al 3+ +Ce 3+ ) was added to the above-prepared solution in a molar ratio of 1:5 and stirred vigorously; di-n-propylamine was added to the solution as a template agent according to the template agent: (Al 3+ +Ce 3+ ) Add the template in a molar ratio of 2:1 and stir vigorously. Add a small amount of di-n-propylamine and adjust the pH value of the white emulsion to 5.0-6.5.

[0056] (2) Under vigorous stirring conditions, evaporate the water in the emulsion at 90-100°C until only a very small amount of water remains. Dry the dry latex at 100-110°C to a dry glue state, grind the dried dry glue, and then place it in a crystallization kettle, crystallize it at 200-210°C for 24 hours, cool it to room temperature, take out the white powder, wash it thoroughly until the filtrate is neutral, and then place the remaining white bottom mud in an oven at 100-110°C for 12 hours, then heat it in a muffle furnace at a rate of 5-8°C / min to 600°C, and continue calcining for 4 hours. After removing the di-n-propylamine template, Ce is prepared. 3+ -Al 3+ Doped SF6 degradation catalyst.

[0057] 2. Degradation performance test:

[0058] For this example, Ce 3+ -Al 3+ The performance of the doped SF6 degradation catalyst was tested. 0.9g of catalyst was filled in the reaction bed with a particle size of 40-60 mesh. A mixed gas was passed through at an air velocity of 15mL / min. The mixed gas contained 1vol% SF6, 2vol% H2O, 1vol% O2, and 96vol% N2. The tests were carried out at 600℃, 650℃, 700℃, and 750℃, and the SF6 degradation rates were 34%, 58%, 71%, and 95%, respectively.

[0059] Example 2

[0060] 1. Catalyst preparation:

[0061] The catalyst preparation is different from that in Example 1 only in that the Al 3+ +Ce 3+ The amount of substance remains unchanged, pseudo-boehmite and cerium nitrate are calculated according to Al 3+ :Ce 3+ The molar ratio was 5:1, and the rest was the same to obtain Ce. 3+ -Al 3+ Doped SF6 degradation catalyst.

[0062] 2. Degradation performance test:

[0063] For this example, Ce 3+ -Al 3+ The performance of the doped SF6 degradation catalyst was tested. 0.9g of catalyst was filled in the reaction bed with a particle size of 40-60 mesh. A mixed gas was passed through at an air velocity of 15mL / min. The mixed gas contained 1vol% SF6, 2vol% H2O, 1vol% O2, and 96vol% N2. The tests were carried out at 600℃, 650℃, 700℃, and 750℃, and the SF6 degradation rates were 55%, 72%, 93%, and 100%, respectively.

[0064] Example 3

[0065] 1. Catalyst preparation:

[0066] The catalyst preparation is different from that in Example 1 only in that the Al 3+ +Ce 3+ The amount of substance remains unchanged, pseudo-boehmite and cerium nitrate are added at a molar ratio of Al:Ce of 5:2, and the rest are the same to obtain Ce 3+ -Al 3+ Doped SF6 degradation catalyst.

[0067] 2. Degradation performance test:

[0068] For this example, Ce 3+ -Al 3+ The performance of the doped SF6 degradation catalyst was tested. 0.9g of catalyst was filled in the reaction bed with a particle size of 40-60 mesh. A mixed gas was passed through at an air velocity of 15mL / min. The mixed gas contained 1vol% SF6, 2vol% H2O, 1vol% O2, and 96vol% N2. The tests were carried out at 600℃, 650℃, 700℃, and 750℃, and the SF6 degradation rates were 41%, 62%, 75%, and 92%, respectively.

[0069] Example 4

[0070] 1. Catalyst preparation:

[0071] The catalyst preparation was different from that in Example 1 only in that the amount of (Al+Ce) in step (1) was kept unchanged, pseudo-boehmite and cerium nitrate were added at a molar ratio of Al:Ce of 7:1, and the rest was the same to obtain Ce 3+ -Al 3+ Doped SF6 degradation catalyst.

[0072] 2. Degradation performance test:

[0073] For this example, Ce 3+ -Al 3+ The performance test of the doped SF6 degradation catalyst was carried out by filling 0.9g of the catalyst in the reaction bed with a particle size of 40-60 mesh, passing the mixed gas at an air velocity of 15mL / min, and the mixed gas contained 1vol% SF6, 2vol% H2O, 1vol% O2, and 96vol% N2, and the tests were carried out at 600℃, 650℃, 700℃, and 750℃, respectively. The degradation rates of SF6 at 600℃, 650℃, 700℃, and 750℃ were 60%, 95%, 100%, and 100%, respectively.

[0074] Comparing Examples 1 to 4, the different doping ratios of the two metal elements have a greater impact on the catalytic performance. 3+ :Ce 3+ The best degradation performance was shown when the molar ratio was 7:1.

[0075] Among the above four examples, Example 4 exhibits the most excellent SF6 degradation performance, and only the catalyst in Example 4 is further selectively tested here.

[0076] 3. Select performance test:

[0077] Sodium hydroxide solution is used as the absorption liquid. The absorption liquid concentration should be between 1.0-2.0 mol / L. The gas flow out of the absorption bed is absorbed. x The selectivity performance is evaluated by measuring the percentage of sulfur oxides (including sulfur dioxide, sulfur trioxide, etc.) in the total amount of sulfur-containing compounds in the product.

[0078] This test uses S balance to calculate SO x Selective, only SO is tested in the test x Calculated by the following formula,

[0079]

[0080] In the formula, SOx s For SO x Selectivity, %, S 测 SO in the absorption solution determined by ion chromatography x The mass of S after conversion of the component, mg, S 总 It is the mass of S corresponding to SF6 in the reactor bed inlet gas after conversion, mg.

[0081] S 测 =0.4C1V1

[0082] Where C1 is the SO in the absorption liquid x Concentration, mg / L, V1 is the volume of absorption liquid, L.

[0083]

[0084] Where A is the proportion of SF6 in the mixed gas inlet to the reaction bed, U is the flow rate of the mixed gas inlet to the reaction bed, mL / min, T is the time for the absorption liquid to absorb the gas out of the reaction bed, min, V m is the molar volume of gas at a certain temperature, which is 24.5L / mol at 25℃.

[0085] The test results show that the absorption liquid does not contain SO4 2- , SO3 was detected 2-, indicating that the SO x All are SO2.

[0086] The test results of the catalyst performance of Example 4 are as follows: at 750°C, the selectivity of the catalyst for SO2 reaches 100%, at 700°C, the selectivity of the catalyst for SO2 is about 60%, and at 650°C, the selectivity of the catalyst for SO2 is about 33%.

[0087] Comparative Example 1

[0088] 1. Catalyst preparation:

[0089] The preparation method of the SF6 degradation catalyst involved in this comparative example includes the following steps.

[0090] (1) Pseudo-boehmite (Al2O3 content 70wt%) was added to an appropriate amount of deionized water and fully dissolved, and the solution was vigorously stirred until it became a white emulsion; according to PO4 3- :Al 3+ The phosphoric acid solution was added to the white emulsion in a molar ratio of 1:1 and stirred vigorously; 4+ :Al 3+ The acidic silica sol was added to the above prepared solution in a molar ratio of 1:5 and stirred vigorously; the template:Al 3 + Add di-n-propylamine as a template to the solution at a molar ratio of 2:1 and stir vigorously. Add a small amount of di-n-propylamine dropwise to adjust the pH value of the white emulsion to 5.0-6.5.

[0091] (2) Under vigorous stirring conditions, evaporate the water in the emulsion at 90-100°C until only a very small amount of water remains. Dry the dry latex at 100-110°C to a dry glue state, grind the dried dry glue, and then place it in a crystallization kettle, crystallize it at 200-210°C for 24 hours, cool it to room temperature, take out the white powder, wash it thoroughly until the filtrate is neutral, and then place the remaining white bottom mud in an oven at 100-110°C for 12 hours, then heat it in a muffle furnace at a rate of 5-8°C / min to 600°C, and continue calcining for 4 hours. After removing the di-n-propylamine template, the SF6 degradation catalyst described in Comparative Example 1 is prepared.

[0092] 2. Degradation performance test:

[0093] The performance of the SF6 degradation catalyst of Comparative Example 1 was tested. 0.9 g of the catalyst was filled in the reaction bed with a particle size of 40-60 mesh. A mixed gas was passed through the catalyst at an air velocity of 15 mL / min. The mixed gas contained 1 vol% SF6, 2 vol% H2O, 1 vol% O2, and 96 vol% N2. The tests were carried out at 600°C, 650°C, 700°C, and 750°C, and the SF6 degradation rates were 30%, 46%, 66%, and 79%, respectively.

[0094] 3. Select performance test

[0095] Referring to the selectivity test of the catalyst in Example 4, the performance test results of the catalyst in Comparative Example 1 are as follows: no SO was detected in the samples collected at 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, and 800°C. x , that is, SO of the catalyst prepared in Comparative Example 1 x Selectivity is 0.

[0096] Comparative Example 2

[0097] 1. Catalyst preparation:

[0098] The SF6 degradation catalyst involved in this comparative example is different from that in comparative example 1 only in that the pseudo-boehmite in step (1) is completely replaced by an equimolar amount of cerium nitrate, and there are no other differences, thereby obtaining a SF6 degradation catalyst.

[0099] 2. Degradation performance test:

[0100] The performance of the SF6 degradation catalyst of Comparative Example 2 was tested. 0.9 g of the catalyst was filled in the reaction bed with a particle size of 40-60 mesh. A mixed gas was passed through the catalyst at an air velocity of 15 mL / min. The mixed gas contained 1 vol% SF6, 2 vol% H2O, 1 vol% O2, and 96 vol% N2. The tests were carried out at 600°C, 650°C, 700°C, and 750°C, and the SF6 degradation rates were 50%, 82%, 92%, and 100%, respectively.

[0101] Comparing Examples 1 to 4, Comparative Example 1 and Comparative Example 2, the best degradation performance is shown under the conditions of Example 4, and the degradation rates of SF6 at 600°C, 650°C, 700°C and 750°C are 60%, 95%, 100% and 100% respectively. Comparing Example 4 with Comparative Example 1, better SO x Selectivity performance: at 750°C, the catalyst's selectivity for SO2 reaches 100%, at 700°C, the catalyst's selectivity for SO2 is about 60%, and at 650°C, the catalyst's selectivity for SO2 is about 33%.

[0102] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a sulfur hexafluoride degradation catalyst, characterized in that: Includes steps: (1) adding pseudo-boehmite and / or cerium nitrate into deionized water to fully dissolve, and stirring until an emulsion or solution is formed; then adding phosphoric acid, a silicon source and a template agent in sequence under stirring, and adjusting the pH value of the mixed solution to 5.0-6.5; (2) stirring and evaporating the water in the mixed solution obtained in step (1), and further drying to obtain a dry glue; grinding the dry glue and placing it in a crystallization kettle, crystallizing at 200-210° C., washing the crystallized product to neutrality and then drying it, calcining it to remove the template agent, and obtaining an Al and / or Ce doped SF6 degradation catalyst.

2. The preparation method according to claim 1, characterized in that: In step (1), pseudo-boehmite and cerium nitrate are added in an Al:Ce molar ratio of 10:(1-4).

3. The preparation method according to claim 1, characterized in that: In step (1), pseudo-boehmite and cerium nitrate are added in an Al:Ce molar ratio of 7:

1.

4. The preparation method according to claim 1, characterized in that: In step (1): The mass content of Al2O3 in the pseudo-boehmite is 65% to 70%; The conductivity of the deionized water is not greater than 20.0 μS / cm; Press PO4 3- :(Al 3+ +Ce 3+ ) add phosphoric acid in a molar ratio (0.98-1.02):1, preferably 1:1; Phosphoric acid is added in the form of phosphoric acid solution; The phosphoric acid content in the phosphoric acid solution is not less than 85% by mass; Press Si 4+ :(Al 3+ +Ce 3+ ) add silicon source in a molar ratio (0.95-1.05):5, preferably 1:5; The silicon source is at least one of acidic silica sol and tetraethyl orthosilicate; The pH of the acidic silica sol is 2.2 to 3.6; The mass content of SiO2 in the acidic silica sol is 29% to 31%; By template: (Al 3+ +Ce 3+ ) add the template in a molar ratio of 2:(1-1.05) preferably 2:1; The template agent is at least one of di-n-propylamine and diisopropylamine; At least one of di-n-propylamine and diisopropylamine is used to adjust the pH value of the mixed solution.

5. The preparation method according to claim 1, characterized in that: In step (2): The crystallization time at 200-210°C is 20h-24h, preferably 24h; The heating rate of the calcination is 5-8°C / min, the insulation temperature is 550-600°C, and the insulation time is 4h-5h.

6. An Al and / or Ce doped SF6 degradation catalyst prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the Al and / or Ce doped SF6 degradation catalyst according to claim 6 in catalytic degradation of SF6.

8. The use according to claim 7, characterized in that: The temperature of the catalytic degradation is 500-800°C; During the catalytic degradation process, H2O and / or O2 also exist in the catalytic degradation environment.

9. A method for catalytic degradation of SF6, characterized in that: include: The mixed gas containing SF6 is passed through the Al and / or Ce doped SF6 degradation catalyst as claimed in claim 6 to catalytically degrade SF6.

10. The method according to claim 9, characterized in that The mixed gas contains H2O and / or O2; The temperature of the catalytic degradation is 500-800°C.

Citation Information

Patent Citations

  • Catalyst and method for decomposition of perfluoro-compound in waste gas

    CN100389857C

  • A method for treating sulfur hexafluoride waste gas

    CN110124512B

Cited By

  • Plasma catalyst suitable for sulfur hexafluoride degradation and preparation and application thereof

    CN122321893A